King Hussein bin Talal's military strategy 1953-1956 (documentary study) (Journal of the College of Basic Education, 2022)
King Hussein bin Talal is a distinguished political, military and administrative figure, a distinguished leader among Arab leaders. With his diplomacy, pragmatism, he served national causes through the method of appeasement with Britain, which was controlling the country through the treaties signed between them. King Hussein bin Talal was able to Arabize the Jordanian army and complete the country's independence at costs less than those incurred by most Arab countries in achieving their independence.King Hussein was able to assume the duties of government and the position of commander-in-chief of the Jordanian Armed Forces simultaneously, being a graduate of the Sandhurst Academy for Military Sciences in Britain. He invested that experience in developing the Jordanian military institution and delivering it to what it has reached. It has now strength and modernization, which has proven its ability to defend and maintain security and stability in the country in the most challenging and complex circumstances it has gone through. Perhaps this is due to King Hussein’s political and military strategy, personality, and leadership